Influenza vaccination is associated with a decreased risk of atrial fibrillation: A systematic review and meta-analysis - Liu, Menglu; Lin, Weichun; Song, Tiangang; Zhao, Huilei; Ma, Jianyong; Zhao, Yujie; Yu, Peng; Yan, Zhiwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Evidence from longitudinal studies have shown that influenza infection is linked to an increased risk of arrhythmia. Therefore, we aimed to assess the role of influenza vaccination in arrhythmia prevention. Methods: The PubMed, Embase, and Cochrane Library databases were searched to identify studies that investigated the potential effects of the influenza vaccine on arrhythmia risk that were published until October 25th, 2021. The study was registered with PROSPERO (CRD42022300815). Results: One randomized controlled trial (RCT) with 2532 patients and six observational studies with 3,167,445 patients were included. One RCT demonstrated a nonsignificant benefit of the influenza vaccine on arrhythmias (odd ratio [OR] = 0.43, 95% confidence interval [CI]: 0.11-1.64; P = 0.20) in patients after myocardial infarction or those with high-risk stable coronary heart disease. A meta-analysis based on observational studies showed that vaccination was associated with a significantly lower risk of arrhythmia (OR: 0.82, 95% CI: 0.70 to 0.97; P = 0.02; I2=76%). Additionally, subgroup analysis showed a decreased risk of atrial fibrillation (OR: 0.94, 95% CI: 0.90-0.98; P = 0.006; I2= 0%) and a nonsignificant but positive trend concerning ventricular arrhythmias (OR: 0.68, 95% CI: 0.42-1.11; P = 0.12; I2=85%) after influenza vaccination. Conclusion: Based on the current evidence, influenza vaccination may be associated with a reduced risk of arrhythmia, especially atrial fibrillation. Influenza vaccination may be an effective tool for the prevention of arrhythmias. The effect of influenza vaccination on ventricular arrhythmias and arrhythmias in patients at low risk cardiovascular diseases should be further studied.